Non-Aboriginal Child Protective Service Workers’ Utilization of the Maltreatment and Adolescent Pathway Knowledge Translation (MAP-KT) Portal: A Report on the Utilization Statistics and Utilization Gaps of Aboriginal Best-Practice Material - Leung, Eman; Wekerle, Christine; Weachter, Randy; Egelstaff, Julian; Bennett, Marlyn (First Peoples Child & Family Review)

(untitled) (First Nations Child and Family Caring Society of Canada, 2011)
Given the unique history and culture of the Aboriginal heritage, research evidence and evidence-based practice guidelines/recommendation derive from the general population are not sufficient in informing the practices of Child Protective Services’ caseworkers who are caring for Aboriginal youth in the child welfare system. Special attention should also be given to best-practice materials developed with special consideration of the Aboriginal context. The current study describes caseworkers’ utilization of Aboriginal child welfare best-practice materials hosted at the MAP-KT portal during its pilot testing period between October 1st 2007 and September 31st 2008. The objective of the current study is to assess the knowledge consumption behavior of caseworkers who were not employed by Aboriginal child protective agency but nonetheless had Aboriginal Child Welfare youth under they care. The MAP-KT portal is a web-based knowledge tool that brings to the point of practice (of CPS caseworker) child welfare knowledge distilled through the ‘knowledge filter” of the Knowledge to Action framework. Given the proportion of Aboriginal youth under the care of participating agencies, the utilization statistics of Aboriginal content hosted on the MAP-KT portal indicated that they might be under-utilized compared to other content areas. According to the Knowledge to Action framework, a number of ways to improve utilization have been proposed. Future research may focus on adapting the MAP-KT portal to user knowledge preferences on format, content and linkage to frequently utilized sites, as well as tailored marketing to users in First Nations child welfare services and those who provide services to children with First Peoples’ heritage.